Losartan as a mechanotherapeutic adjuvant: Remodeling the breast tumor microenvironment to improve treatment efficacy - Mutaz Dwairy; Alaa Yehya; Feras M. Mohammad; Hiba Alzoubi (PLoS ONE, 2025)
Tumor stiffness is a critical factor influencing cancer progression, therapeutic resistance, and drug delivery. This study investigates the role of mechanical normalization in breast cancer therapy through the anti-fibrotic action of losartan, an angiotensin II type 1 receptor blocker. We developed a comprehensive multiphysics model integrating tumor cell proliferation, oxygen transport, interstitial fluid dynamics, and losartan pharmacokinetics/pharmacodynamics (PK/PD). Simulations demonstrate that losartan reduces tumor stiffness by up to 28%, enhances oxygenation by 8%, and increases tumor porosity by ~45%, thereby enhancing drug penetration and interstitial transport. Furthermore, tumor cell concentration decreased by 88%, reflecting the drug’s dual anti-proliferative and pro-apoptotic effects. Spatial analyses revealed heterogeneity in stiffness reduction and drug response, emphasizing the importance of tumor geometry and perfusion. Our findings support the potential of losartan as a mechanotherapeutic adjuvant to enhance standard cancer treatments by remodeling the tumor microenvironment and overcoming mechanical barriers to therapy.